Stylistic Analysis of the poem"Leisure" By William Davies - Akhter, Shaheen (JOURNAL OF ADVANCES IN LINGUISTICS, 2017)
The researcher has tried to highlight the dilemma of modern man described in the poem leisure by William Davies. Modern man is so much engrossed in getting and spending that he has no time to see and enjoy the beauty of nature. Nature is present everywhere in its full bloom and splendour but modern man is so much pre-occupied with worldly pursuits and materialistic designs that he has no time to see and enjoy the beauty manifested in various forms. The natural elements present an invitation to man but a modern man,being busy in rat race, refuses their invitation. He has declared blunt refusal to his aesthetic sense and replaced it with lust for money and other worldly designs. Even animals are much better than man because they live in the heart of nature and enjoy its company. God has, no doubt,created man to explore the nature and praise its beauty but modern man has made himself slave of time and gives preference to his evil designs instead of thinking and brooding upon nature and its blessed beauty.